Analysis on damage characteristics and detonation performance of solid rocket engine charge subjected to jet - Song-lin Pang; Xiong Chen; Jin-sheng Xu; Ge-tu Zhaori; Hong-Ying Du (Defence Technology, 2022)
To further explore the damage characteristics and impact response of the shaped charge to the solid rocket engine (SRE) in storage or transportation, protective armor was designed and the shelled charges model (SCM)/SRE with protective armor impacting by shaped charge tests were conducted. Air overpressures at 5 locations and axial acceleration caused by the explosion were measured, and the experimental results were compared with two air overpressure curves of propellant detonation obtained by related scholars. Afterwards, the finite element software AUTODYN was used to simulate the SCM impacted process and SRE detonation results. The penetration process and the formation cause of damage were analyzed. The detonation performance of TNT, reference propellant, and the propellant used in this experiment was compared. The axial acceleration caused by the explosion was also analyzed. By comprehensive comparison, the energy released by the detonation of this propellant is larger, and the HMX or Al particles contained in this propellant are more than the reference propellant, with a TNT equivalent of 1.168–1.196. Finally, advanced protection armor suggestions were proposed based on the theory of woven fabric rubber composite armor (WFRCA).